Air Pollution and Outpatient Treatment and Hospital Admissions for Respiratory Diseases in Children in Southeast Region of Brazil - Castro, Hermano Albuquerque De; Hacon, Sandra De Souza; Gonçalves, Karen Dos Santos; Junger, Washington Leite (IntechOpen, 2011)
None